Our Laparoscopic Surgical technique and experience in treating pediatric inguinal hernia over the past decade - Dheidan Alshammari; Marina Sica; Isabelle Talon; Isabelle Kauffmann; Raphael Moog; Francois Becmeur; Anne Schneider (Wolters Kluwer Medknow Publications, 2020)
Background: Over the past decade, laparoscopic hernia repair was the most performed operation in our department. Equally, it compromises 15% of all pediatric operations performed. We aim, in this study, to review all the cases performed and extrapolate important information like reoccurrences, the incidence of metachronous inguinal hernia, complications amongst other information. Material and Methods: All patients under the age of 18 whom underwent elective laparoscopic hernia repair between 03/01/2007 till the 18/05/2016 were included in our study. We recorded important clinical features and studied their post-operative follow up. Equally reoccurrences, the incidence of metachronous inguinal hernia, complications and other parameters were recorded and studied. Results: A total of 916 patients were operated on during the defined study period. There was a 0.17% reoccurrence rate and a 0.46% incidence of metachronous inguinal hernia. Equally a contralateral patent processus vaginalis was diagnosed and closed in 17.10%. There were no postoperative complications and we had a 0% postoperative hydrocele rate. Conclusion: Laparoscopic hernia repair is safe and carries all the benefits of minimally invasive surgery. We recommend that it is offered to patients and would like to refute previously claimed reports that it carries a higher reoccurrence rate or takes a long time to perform. Our reoccurrence rate of 0.17% is actually lower than many published reoccurrence rates after open repair.